Safety of mRNA COVID‐19 vaccines in patients with well‐controlled myasthenia gravis. Issue 5 (27th August 2022) - Gamez, Josep; Gamez, Alejandro; Carmona, Francesc
Abstract: Introduction/Aims: Data on safety and tolerability of the vaccines against severe acute respiratory virus coronavirus‐2 (SARS‐CoV‐2, or coronavirus disease‐2019 [COVID‐19]) in patients with myasthenia gravis (MG) are currently limited. In this study we investigated the safety of mRNA‐based two‐dose vaccination in a cohort of patients with MG. Methods: This investigation was a prospective observational study of messenger RNA (mRNA)‐based vaccines administered to patients with MG with stable disease. Local and systemic reactogenicity after injection was monitored for each dose administered. The patients were categorized and clinically assessed following the recommendations of the Myasthenia Gravis Foundation of America. Results: Thirty‐six males and 55 females (mean age at first vaccine dose, 58.8 years; standard deviation,  = 17.1 years) received vaccines. Seventy‐two patients (79.1%) were taking one or more immunosuppressant(s). The most frequent adverse effects were injection‐site pain, fatigue, myalgia, chills, fever, and headache. Local and systemic reactions were transient; 58.2% of the patients developed one or more reaction(s). There were no anaphylactic reactions. None of the patients had a myasthenic crisis, and two developed a mild deterioration compared with their Quantitative Myasthenia Gravis baseline score. The clinical outcome scores showed no exacerbation of MG symptoms. Patients over 65 years of age developed fewer adverse effects. COVID‐19 vaccination did not induce clinical exacerbation in stable patients with MG, regardless of their age, sex, history of myasthenic crisis, or whether they were taking immunosuppressants. Discussion: Our data are consistent with the mRNA COVID‐19 vaccine being well tolerated in patients with well‐controlled MG. The findings may contribute to decisions in vaccination campaigns in the future.